EVALUASI KETERLIBATAN MAHASISWA DAN ALUMNI DALAM PEKERJAAN PENGENDALIAN MUTU LAPISAN ASPAL BETON DI KULON PROGO - Nurokhman, Nurokhman; Suharyanto, Indra; Subagyo, Singgih; Purnomo, Joko (Universitas Cokroaminoto Yogyakarta, 2024)
The purpose of the activity is to find out the involvement of students and alumni in quality control of asphalt concrete work. The study method is through site visits, observing work documents and providing work quality control material. The existence of Kerra Practicing students in the field has helped a lot in checking the volume of work and checking the quality. Asphalt concrete test results on the Kokap-Pripih Road Section Improvement project in Kulonprogo Regency have a density of asphalt concrete AC-WC 98.82% > 98% (meet the requirements), the degree of density of asphalt concrete AC-BC 99.12% > 98% (meet the requirements ). The asphalt content of ACWC is 5.6%, the asphalt content of ACBC asphalt is 5.5%. Examination of the thickness at 34 points of the core drill showed that the average thickness of the ACBC layer was 6.17 cm > 6.0 cm (meet the requirements) and the average thickness of the ACWC layer was 4.20 cm (meets the requirements). As a recommendation for construction activities to comply with the construction safety management system by wearing personal protective equipment and work protective equipment.